Universal Health Coverage Acceleration Through the UHC Village Approach: The (Supporting Universal Health Coverage So Express and Sustainable (SUCSES) Innovation in Indonesia’s in National Health Insurance Program - Maihendra; Budhi Mulyadi (CV. Get Press Indonesia, 2025)
Universal Health Coverage (UHC) is a cornerstone global health target, reaffirmed by the World Health Organization (WHO) and the United Nations’ commitment to achieve it by 2030. Despite Indonesia’s sustained national initiatives, structural barriers persist, including membership gaps, subnational disparities, and high out-of-pocket expenditures. This qualitative descriptive study investigates the SUCSES Innovation (Supporting Universal Health Coverage So Express and Sustainable), a decentralized, village-level model designed to accelerate UHC progress. Conducted at the BPJS Kesehatan Bukittinggi Branch from January 2023 to December 2024, the research engaged purposively selected informants: branch managers, local government officials, village leaders, and program implementers. Data collection included in-depth interviews, document reviews, and membership record analysis. Thematic analysis identified governance mechanisms, implementation strategies, and outcome pathways, yielding four themes: (1) institutionalizing UHC targets through village certification frameworks; (2) strengthening subnational governance and accountability; (3) enabling community micro-targeting via data-driven outreach; and (4) achieving gains in coverage and financial performance. SUCSES generated 135,000 new registrations, increased coverage from 87% to 97%, and produced IDR 68 billion in additional revenue.